Implementasi Pendidikan Karakter Disiplin Siswa Kelas III SD Muhammadiyah 11 Randegan, Tanggulangin, Sidoarjo - Sari, Rahma Della; Indrakurnawan, Machful; Sari, Nila Kartika (Universitas Tribhuwana Tunggadewi, 2024)
This study aims to describe the implementation of disciplinary character education for third grade students of Muhammadiyah 11 Randegan Elementary School, Tanggulangin, Sidoarjo. The method used in this research is qualitative research with descriptive type. Data collection techniques used in this study are observation, interviews and documentation. The data sources obtained in this study came from homeroom teachers and third grade students. Data analysis was obtained using the miles and Huberman analysis technique, namely data reduction, data presentation and data conclusion. The results of this study indicate that third grade students of SD Muhammadiyah 11 Randegan can implement disciplinary character education well based on discipline indicators, namely getting used to coming and leaving school on time, orderly marching when entering class, following literacy activities in an orderly manner, obeying the rules that apply in class, wearing school uniforms according to schedule, completing assignments on time, following learning in an orderly manner, performing dhuha and dzhuhur prayers in congregation.